Anfangs-Gründe des General Basses - Mizler, Lorenz Christoph 1711-1778 (Hildesheim G. Olms, 1972)
Lorenz Mizler took his degree in music in 1736 at the University of Leipzig, where he lectured on music history ('Die gelehrte Historie der Musik'), mathematics, and philosophy. Aiming to “confer on music the shape of a science," Mizler lay at the basis of the development of 'Musikwissenschaft'. He was closely connected to Christian Wolff and Johann Mattheson.
Keywords: Basso continuo